Depiction of Nataraja on the Jangha of the Hazareshwar Temple - Temples of India Project Team (Jio Institute, 2024)
Nataraja dances to the rhythm of celestial drummers. He is poised in the urdhvajanu posture, his left foot firmly grounded while his right leg is raised and folded inward. He is depicted with multiple arms adorned with various weapons and attributes. In his upper hands, Nataraja holds a sarpa (snake), a damaru (drum), and a pointed weapon, possibly a shula (spear) or a trishula (trident), symbolizing his mastery over cosmic forces. His frontal right hand is raised near his face in a gesture epitomizing the essence of his divine dance. Despite his broken left hand, Nataraja’s pose continues as he extends his front left hand in the gajahasta gesture, reminiscent of an elephant’s trunk. He is adorned with a jatamukuta (crown of matted hair) and ornaments, including circular earrings, broad necklaces, bangles, and anklets. His lower body is draped in a translucent dhoti with a sash hanging between his legs. Two drummers are carved at the bottom on both sides, adding a touch of celestial rhythm to this tableau.